(untitled) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2021)
Background: Employee satisfaction is always considered a vital component which contributes towards employee performance and employee retention in hotel industry. The factors that bestow to employee satisfaction are dynamic in nature and studies needs to be conducted to find out factors that adds to the satisfaction levels of youngsters joining hotel industry. Objectives: The main purpose of this study was to identify the core factors which contribute towards employee satisfaction for fresher in hotel industry and impact of training on these factors. Methodology: The factors identified were job satisfaction, rewards, promotion, working environment and social aspects of job. The study was conducted towards correlation between these factors and different demographic profiles such as sex, ownership, department, post and qualification of candidates. Samples were collected from hotels with multinational ownership, multinational franchise, Indian chain-ownership/franchise and Indian standalone hotels. Data from four major revenue generating departments- Front office, Housekeeping, Food and Beverage Service and Food Production was taken from 151 candidates with less than two years of industry experience. Data was tested for correlation coefficient, mean, S.D and regression analysis. Results: Main findings were that multinational ownership hotels were efficient in implementing the training functions followed by multi-national franchise, Indian chain hotels were performing satisfactory towards implementation of training for employee satisfaction. There is major gap in implementation of training functions in Indian standalone hotels creating a potential for them to improve towards this aspect of employee satisfaction. Training was found to have positive linear relationship with employee satisfaction.85 male and 66 female candidates took part in the study. Conclusion: Training had strong positive correlation with job satisfaction, working environment, promotion and social aspects whereas moderate relationship was established with rewards. Qualification, management and department were demographic profiles with higher variability whereas sex and post were having medium variability.